2019
DOI: 10.1007/s12088-018-00777-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-digestion of Biowastes to Enhance Biological Hydrogen Process by Defined Mixed Bacterial Cultures

Abstract: Co-digestion of biowastes for hydrogen (H 2 ) production using defined mixed cultures can overcome the high risk of failure due to contamination and imbalanced nutrient status. H 2 production from biowastes-pea-shells, potato peels (PP), onion peels (OP) and apple pomace, either individually or in various combinations was evaluated by hydrolyzing with defined hydrolytic mixed bacterial culture (MHC5) and subjecting the hydrolysate to mixture of defined H 2 producers (MMC6). Co-digestion of OP and PP hydrolysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Various research activities brought up the new technologies for the gasification of biomass substances like sugarcane wastes, food wastes, paper wastes, polyethylene and wood chips, wastewater sludge, and branches of palm oil trees. Also, to enhance the rate of hydrogen production of biomass, various combinations were defined by hydrolyzing the biowaste like onion peels and potato peels with mixed bacterial cultures . Similarly, Fig.…”
Section: Hydrogen Production Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research activities brought up the new technologies for the gasification of biomass substances like sugarcane wastes, food wastes, paper wastes, polyethylene and wood chips, wastewater sludge, and branches of palm oil trees. Also, to enhance the rate of hydrogen production of biomass, various combinations were defined by hydrolyzing the biowaste like onion peels and potato peels with mixed bacterial cultures . Similarly, Fig.…”
Section: Hydrogen Production Processesmentioning
confidence: 99%
“…Also, to enhance the rate of hydrogen production of biomass, various combinations were defined by hydrolyzing the biowaste like onion peels and potato peels with mixed bacterial cultures [29]. Similarly, Fig.…”
Section: Biomass Gasificationmentioning
confidence: 99%
“…The phylogenetic analysis of isolate SS2 carried out using MEGA X software shows that the strain clustered with the different species of Bacillus genus such as Bacillus cereus, Bacillus luti, Bacillus albus, Bacillus mycoides, and Bacillus tropicus (Figure 2). Genus Bacillus is known for its biotechnological applications such as hydrolytic enzymes as well as value added products (Kumar et al, 2013;Patel et al, 2019;Porwal et al, 2008).…”
Section: Screening Of Cgtase Producing Microorganismsmentioning
confidence: 99%
“…The microbial colonization initiates from birth and maintains throughout the life span [1,2]. Various studies have demonstrated important roles of microorganisms in diverse fields, such as fermentation [3,4], biomolecules [5,6], bioremediation [7][8][9][10], anti-toxicity [11,12], and diseases and health [13][14][15][16][17][18]. Pathogenesis, including the recent outbreak of coronavirus, can be effectively treated through the application of these bioactive molecules, vaccines, and nanomaterials [11,14,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%